Growth and Photosynthetic Efficiency of Acacia Mangium Willd and Acacia Aulacocarpa A. Cunn Ex, Benth Multiple Leadered Trees - Mat, Sapari (2008)
Acacia mangium Willd. and Acacia aulacocarpa A. Cum. Ex. Benth are among the two important Acacias planted in Malaysia and both species exhibited multiple-leader (ML). ML is the formation of more than one stems from the base of planted trees which affect the productivity of the stands if they are to be used for timber production. With more volume of wood per tree basis, ML trees were considered as an advantage for pulp and paper industry. However, its productivity and wood quality are still being questionable to the industry. Thus, this study was conducted to evaluate the growth performance after seven years, aboveground biomass (AGB), specific gravity of wood (SGwd) and photosynthetic efficiency of ML trees of these species. Growth performance of seven-year old trees was based on diameter at breast height (Dbh) and height. Then, biomass was estimated fiom a total of 72 trees (2 species x 4 provenances x 3 Dbh classes x 3 replicates. Specific gravity of wood (SGwmd) was then estimated using similar Dbh groupings and also based on three levels of height. In addition, gas exchange was also estimated using similar Dbh groupings between ML and single stemmed trees to establish the light response curve to estimate their maximum rate of photosynthesis (A,,) and quantum yield (@). The growth performance at 7 year-old indicated significant differences at P10.05 between species and provenances with regards to Dbh and height. A. mangium outperformed A. aulacocarpa for both attributes. On the other hand, trees of A. aulacocarpa from PNG provenances performed better than the ones from QLD. There were also significant differences at P10.05 between provenance in terms of stem and total biomass and; between Dbh, dl parameters of AGB of A. mangium. A. mangium fiom SW of Boset WP (PNG) recorded the highest mean of AGB i400.19 kg) and Russel & Gap CK (QLD) recorded the least (202.68 kg). On the other hand, A. aulacocarpa showed significant differences between provenances and Dbh classes for all parameters measured with provenance from Arufi E. Morehaed WP (PNG) gave the highest total AGB (219.72 kg) and provenance from 3K S Mt Larcom, QLD recorded the least (34.12 kg). A. mangium was better than A. aulacocarpa in terms of biomass production. In addition, eight regression equations to estimate aboveground biomass and revealed that Dbh is the main factor affecting the production of the different provenances. Generally, SGwWd of A. aulacocarpa was higher than the ones produced by A. mangium especially from lower part of trees. There was also significant difference between height levels with regards to provenance and Dbh classes. Generally, the order of SGwmd production for both species is bottom> middle> top. Moreover, there was no significant difference at P10.05 between provenances, growth habits (ML and SS), Dbh classes and their interaction in terms of A,,. Similar statistical analyses were also obtained for quantum yield except for between provenances of A. mangium. Based on composite ranking of all attributes revealed that A. mangium from SW of Boset (PNG), Captain Billy Road (QLD) and Bensbach WP (PNG) and A. aulacocarpa from Arufi E. Morehaed WP (PNG) and W. Morehead (PNG) showed relatively good performance and indicated their suitability and robustness to local environment. The results also revealed that growth performance was positively correlated with AGB but not for SGwmd, A,, and quantum yield between species and provenances. Thus, the above potential provenances should be considered in breeding programme of Acacia species for the purpose of high yield productivity.